TRPM4-dependent post-synaptic depolarization is essential for the induction of NMDA receptor-dependent LTP in CA1 hippocampal neurons - Menigoz, Aurélie; Ahmed, Tariq; Sabanov, Victor; Philippaert, Koenraad; Pinto, Silvia; Kerselaers, Sara; Segal, Andrei; Freichel, Marc; Voets, Thomas; Nilius, Bernd; Vennekens, Rudi; Balschun, Detlef (Pflügers Archiv, 2016)
TRPM4 is a calcium-activated but calcium-impermeable non-selective cation (CAN) channel. Previous studies have shown that TRPM4 is an important regulator of Ca2+-dependent changes in membrane potential in excitable and non-excitable cell types. However, its physiological significance in neurons of the central nervous system remained unclear. Here, we report that TRPM4 proteins form a CAN channel in CA1 neurons of the hippocampus and we show that TRPM4 is an essential co-activator of N-methyl-d-aspartate (NMDA) receptors (NMDAR) during the induction of long-term potentiation (LTP). Disrupting the Trpm4 gene in mice specifically eliminates NMDAR-dependent LTP, while basal synaptic transmission, short-term plasticity, and NMDAR-dependent long-term depression are unchanged. The induction of LTP in Trpm4−/−neurons was rescued by facilitating NMDA receptor activation or post-synaptic membrane depolarization. Accordingly, we obtained normal LTP in Trpm4−/−neurons in a pairing protocol, where post-synaptic depolarization was applied in parallel to pre-synaptic stimulation. Taken together, our data are consistent with a novel model of LTP induction in CA1 hippocampal neurons, in which TRPM4 is an essential player in a feed-forward loop that generates the post-synaptic membrane depolarization which is necessary to fully activate NMDA receptors during the induction of LTP but which is dispensable for the induction of long-term depression (LTD). These results have important implications for the understanding of the induction process of LTP and the development of nootropic medication.
Published online: 3 December 2015
Gesehen am 05.05.2020